Transforming livestock production: unraveling the impact of socioeconomic dynamics and land use changes in Khost Province - Ahmadzai, Mujib Rahman; Ismail, Mohd Hasmadi; Hassan Zaki, Pakhriazad; Magiman, Mohd Maulana; Bawon, Paiman; Rahmawaty; Ullah, Hayat (Taylor and Francis, 2025)
This study examines the impact of socio-economic factors and land-use changes on livestock production among rural communities in Khost Province, Afghanistan. Data were collected from 687 livestock owners across five districts (Gurbuz, Khost ‘Matun,’ Mandozayi, Musakhel, and Qalandar) using a structured questionnaire. Analytical techniques, including Univariate ANOVA, MANOVA, and binary logistic regression, were applied. Findings reveal that key socio-economic factors—such as age, household size, homeownership, and income—significantly influence livestock farming. Farmers with access to modern infrastructure and experiencing natural land-use shifts reported positive effects on livestock production. The study highlights that cows, sheep, goats, donkeys, horses, and fish are integral to farming practices, with cow and fish owners primarily viewing their livestock as income sources. These insights underscore the need for targeted interventions by the government and development organizations to enhance sustainable livestock farming, ultimately improving livelihoods and economic stability in rural Afghanistan.